Crossing the metabolic homeostasis divide: panoramic decoding of therapeutic targets for metabolic-inflammatory crosstalk in rheumatoid arthritis - Liang, Siyu; Wan, Lei; Wang, Siyu; Zhang, Mengyu; Wang, Ying; Min, Wenwen; Zhang, Yu (Frontiers in Immunology, 2025)
Rheumatoid arthritis (RA) is an autoimmune disease characterized by chronic inflammation and joint destruction. Its pathogenesis is closely related to the imbalance of glycolipid metabolism. This article reviews the pathophysiological mechanisms of glycolipid metabolism in the RA pathogenesis, focusing on the physiological mechanisms of glucose and lipid metabolism as well as the characteristics of glycolipid metabolism imbalance and their interactions in RA. Moreover, this study highlights the relationship between specific glycolipid metabolism markers and disease activity, as well as the innovative targets and intervention strategies of glycolipid metabolism modulation in the RA treatment. Studies show that RA patients have over-activated glycolytic pathways and disrupted lipid metabolism. These metabolic changes drive the inflammatory response and joint destruction and are also strongly associated with disease activity. Through a deeper understanding of the key nodes and regulatory mechanisms of glycolipid metabolism in RA, this article might provide new ideas for the precise diagnosis and treatment of RA.